NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM FILM KARTUN NUSSA DAN RARA (STUDI DOKUMENTER AKHLAK IKHLAS ANAK USIA DINI) - Anantia, Rosa Amalina; Soekmono, Roostrianawahti (Jurnal Caksana : Pendidikan Anak Usia Dini, 2022)
The Nussa and Rara films are films that have high moral and educational values in each episode, especially those of Islamic religious values, one of which is the values of sincere morals. The documentary study was carried out on three episodes of the Nussa and Rara films which contain values of sincere morals, namely the episodes of Belajar Ikhlas, Tak Bisa Balas and Nussa Bisa. The research method used is a documentary study with the following stages: the first stage, pre-research by identifying the episodes in season 1 and 2 that contain sincere moral values and describing the storyline of the selected episodes. Stage two, the research design by compiling the lattice instruments, film curation instruments and expert judgment instruments. Stage three, conducting research by curating films by 4 curators, after which the results of the curation were coded to get a method of instilling sincere moral values in the Nussa and Rara films.The results of this documentary study research are that there are three methods of cultivating sincere morals in the Nussa and Rara films, namely the Habitual Method, the Tabyin Method, and the Exemplary Method.